Isotopic Tracers for Combustion Research. Issue 4 (3rd April 2017) - Eveleigh, Aaron; Ladommatos, Nicos
ABSTRACT: This review article deals with the use of isotopic tracers in the field of combustion science. A number of researchers have reported the use of isotopic techniques, which have been employed to solve a wide range of combustion problems. Radioactive and stable isotopes have been utilized as tracers, including isotopes of carbon ( 13 C and 14 C), oxygen ( 18 O), and deuterium (D). One of the main applications has been to quantitatively determine the propensity of a molecule in a mixture, or specific atom within a molecule, to form pollutant emissions. Tracer studies have also been used for the elucidation of combustion reaction pathways, and kinetic rate constant determination of elementary reactions. A number of analytical techniques have been used for isotope detection; and the merits of some of the different techniques are discussed in the context of combustion research. This article concludes by exploring emerging methods and potential future techniques and applications.